Harmonization of interests during Arctic industrial development: The case of mining corporation and indigenous peoples in Russia - Novoselov, Andrey; Potravny, Ivan; Novoselova, Irina; Gassiy, Violetta; Sharkova, Antonina (Polar Science, 2023)
The article discusses the mechanism of coordination and harmonization of the interests between indigenous peoples and a mining company during projects implementation on the Arctic industrial development. The purpose of the study is to substantiate methodological approaches for taking into account the interests of the local population when choosing compensation projects in the area of planned mining activities. The hypothesis of the study is the possibility of finding compromise options between field development and economic interests of the local community. The case of extraction project in Anabar national (Dolgan-Evenki) region of Yakutia shows that insufficient consideration of the indigenous interests can lead to conflicts. The methodology of the research consists of the concept of benefit sharing, impact assessment, sociological research. To assess the degree of interaction between the mining company and the local community, a matrix of the balance of their interests has been developed, coupled with an optimization model for the formation of an optimal set of compensation projects. In Results the authors present the methodological tools to provide economic guarantees of the rights of the indigenous peoples during Arctic industrial development. journal article